Pengaruh good corporate governance terhadap profitabilitas perusahaan - Suci Subiyanti; Rachma Zannati (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
The purpose of this study is to provide empirical evidence regarding the effect of the size of the Independent Commissioners and Managerial Ownership on Profitability as measured by ROA. The object of this study is a banking company listed on the Stock Exchange in the 2013-2017 period. Based on the purposive sampling method that is based on the criteria that have been determined, 15 companies were obtained as research samples. The analysis technique uses panel data regression using E-Views 9 software. The results of the study prove that the Independent Board of Commissioners has no significant effect on profitability, while managerial ownership has a significant effect on profitability. Implications and suggestions are explained in this study.